Misconception Analysis of Student Teacher Candidates Using Certainty of Response Index (CRI) and Interviews on the Subject of Calculus 1: Mapping by Gender - Fajar Gayuh Mulyani; Arif Muchyidin; Toheri (MASI Mandiri Edukasi, 2022)
This study aims to: 1) identify the misconceptions that occur in prospective students of mathematics teachers on the subject of calculus 1. 2) identify the misconceptions that occur in prospective students of mathematics teachers about the subject of calculus one based on gender. 3) find out the extent to which misconceptions occur in prospective mathematics teacher students on the subject of calculus 1. The research method used is descriptive with a quantitative approach. The population in this study were students majoring in mathematics education at one of the universities in Cirebon. The research instrument used was a written test in the form of essay questions accompanied by a confidence level column (CRI) and interviews. The results of the study found that the percentage of students who experienced misconceptions on the subject of calculus 1 with the limit function and derivative test material was 15.49% and smaller than the percentage of students who did not know the concept who got a rate of 42.76% and students who understood the concept well that is equal to 22.56%. The rest of the students who know the concept but are not sure get a percentage of 8.08%. While the percentage of misconceptions experienced by female students is 16.35%, for male students is 19.048%. The most common misconception among mathematics students is the concept of the derivative chain rules.